2018
DOI: 10.3390/polym10121388
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Pt-Catalyst by Poly(p-phenylenediamine) Nanocomposites Assisted by Microwave Radiation for Proton Exchange Membrane Fuel Cell

Abstract: The Pt elements are prepared via the redox reaction with microwave (MW) irradiation in the presence of poly(p-phenylenediamine) (PpPD) which is polymerized on XC72 carbon matrix (PpPD/XC72), behaving as reducing agent. The free primary amines of PpPD are actually converted (oxidized) to secondary ones (5,10-dihydrophenazine) after MW irradiation. Transmission electronic microscopy (TEM) micrographs reveal the prepared Pt nanoparticles are well-dispersed on the carbon matrix like commercial Pt-implanted carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Therefore, the reduction reactions for preparing Pt nanoparticles are usually carried out in the presence of conducting carbon black (CB), and this results in the so-called Pt/C products [1][2][3][4][5]. To avoid the residue of metal ions from the inorganic reducing agent, some amine-based organic compounds behave as reducing agents during Pt nanoparticle preparation through hydrothermal [6][7][8], microwave-assisted heating [9,10], or calcination [11]. However, the bulk conductivity of the Pt nanoparticle implanted matrix will be low if the implanted matrix is made of nonconducting carbon materials.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the reduction reactions for preparing Pt nanoparticles are usually carried out in the presence of conducting carbon black (CB), and this results in the so-called Pt/C products [1][2][3][4][5]. To avoid the residue of metal ions from the inorganic reducing agent, some amine-based organic compounds behave as reducing agents during Pt nanoparticle preparation through hydrothermal [6][7][8], microwave-assisted heating [9,10], or calcination [11]. However, the bulk conductivity of the Pt nanoparticle implanted matrix will be low if the implanted matrix is made of nonconducting carbon materials.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, reduction reactions from the Pt ions to Pt nanoparticles are usually carried out in the presence of conductive CBs, leading to Pt/C [ 1 , 2 , 3 , 4 ]. For convenience, certain amino organic chemicals could also behave like reducing agents to prepare Pt nanoparticles by hydrothermal methods [ 5 , 6 , 7 ], microwave-assisted heating [ 8 , 9 ], or often calcination [ 10 ]. However, to improve the electron transport ability (conductivity) of Pt-nanoparticles deposited on non-conductive carbonaceous substrates, calcination in the absence of air is required to convert most of the sp3-carbon substrates into the conjugated sp2-carbon system (more aromatic structures).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that nitrogen doping of a carbon support makes it possible to create additional oxygen electroreduction active sites (surface fragments containing nitrogen atoms in pyrrole and pyridine). First of all, this has a positive effect on the activity of platinum-free and platinum-carbon catalysts in alkaline media [34][35][36][37]. The presence of nitrogen-containing groups on the support surface can also improve the uniformity of the platinum nanoparticles' distribution during the wet synthesis of Pt/C catalysts [38].…”
Section: Introductionmentioning
confidence: 99%